On a criterion of markovity for stochastic processes - Grigelionis, B. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Б. Григелионис. Об одном критерии марковости для случайных процессов B. Grigelionis. Apie vieną markoviškumo kriterijų atsitiktiniams procesams